Balap Karung Sebagai Strategi Latihan Berbasis Permainan untuk Meningkatkan Daya Ledak dan Keseimbangan Atlet Senam Usia Dini - Muhammad Fitrah Mubarak; Swandika Pinem; Abdul Bashir Nur Hasani; Fachrun Nisa Sofiyah Khasanah; Indra Yudistira; Astini Asri; Toni Kogoya (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aims to test the effectiveness of sack race training as a game-based training strategy in improving explosive power and balance in early age gymnasts (6-9 years) compared to conventional training methods. The method used was quantitative with a quasi-experimental design in the form of a pretest-posttest control group design. The sample consisted of 30 gymnasts who were divided into two groups: the experimental group (sack race training) and the control group (conventional training). The intervention was carried out twice per week for 12 meetings. The instruments used were the Vertical Jump to measure explosive power and the Stork Stand Test to measure balance. Data analysis used the Mann Whitney test for explosive power and the Independent t-test for balance at a significance level of 0.05. The results showed that the experimental group experienced an increase in explosive power of 16.20 (p = 0.004) and an increase in balance of 20.58 (p = 0.026), while the control group only increased explosive power by 8.24 and balance by 8.62. The conclusion of this study is that sack racing training significantly improves explosive power and balance in young gymnasts and is more effective than conventional methods. Sack racing is recommended as a fun, measurable training alternative for children's gymnastics coaches. Keywords: Sack Race, Explosive Power, Balance, Early-Age Gymnasts